TINGKAT EFIKASI DIRI MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING - Cindy Pravesti; Elia Firda Mufidah; Maghfirotul Lathifah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This study aims to describe the level of academic self-efficacy of students of the Guidance and Counseling Study Program at PGRI Adi Buana University, Surabaya. The research samples were taken randomly in the 2020, 2021 and 2019 batches. This study used a descriptive quantitative approach using a self-efficacy scale. Data analysis used descriptive analysis with the help of SPSS. The results of the analysis show that the self-efficacy level of students in class 2019 is 93.37, class 2020 is 93.81 and class 2021 is 94.19. Individuals who have high self-efficacy are expected to perform better than individuals who are low, but in some conditions high self-efficacy can reduce effort on a task due to overconfidence, and thus lead to lower performance.